Digital‑Era Parenting: Communication Patterns and Socio‑Emotional Development of Early Childhood Generation Alpha - Nadya, Afla; Irma, Ade (ISTIFHAM, 2026)
This study examines parental communication patterns in the development of socio-emotional skills among early childhood Generation Alpha in the digital era. Through a qualitative, phenomenological-critical approach involving 12 parents in Meulaboh, this research reveals three dominant communication patterns. The findings indicate: an integrative digital mediation combining active guidance with Islamic values; communication dissonance between ideal values and actual parental practices in digital contexts; and strategic technology appropriation for emotional-spiritual socialisation. The empirical findings were dialogically analysed with Qur'anic principles, particularly Q.S. Luqman regarding communication wisdom, Q.S. Al-Isra' concerning speech ethics, and Q.S. Al-Baqarah on moderation principles. This study contributes to the development of a value-based digital parenting model relevant to Indonesian Muslim families. Practical implications include the development of Islamic digital literacy programs that can assist parents in balancing technology use with children's holistic character development.